Effect of Long and Short Term HgbA1c on Surgical Treatment Outcomes of Diabetic Patients with Emergent Foot and Ankle Surgery. Issue 1 (January 2022) - Gotewal, Sunny; Panchbhavi, Vinod K.; Jupiter, Daniel
Category: Ankle; Diabetes; Midfoot/Forefoot Introduction/Purpose: Elevated HgbA1c are associated with higher postoperative complications. It is not as well understood whether the HgbA1c levels measured at the time of surgery, or those measured in the months prior to surgery, are more strongly associated with complications. We carried out a study of our EMR examining whether historic HgbA1c and burden of diabetes, are more or less impactful than more proximately measured HgbA1c. Methods: We identified patients using CPT codes for ankle, tibia, fibula, and femur fracture repair. Similarly, post-operative complications (infection, dehiscence, DVT, PE and SSI) were retrieved using ICD 9 and 10 codes. Variables recorded were comorbidities and complications, age, sex, race, ethnicity, marital status, and HgbA1c. HgbA1c was noted within a month before and a month after repair, and within 18 months and 6 months before repair. For each complication, the association with every other variable was assessed using t-test or chi-squared/Fisher's exact tests, for continuous and categorical variables, respectively. Results: 20 patients had the data needed to carry out the analysis. While t-test revealed no significant differences between those with and without complications, either in terms of long or short term HgbA1c, the differences between HgbA1c at a year prior to surgery appear to be larger. Conclusion: Given that differences between historic HgbA1c in those with and without complications appear to be larger than the differences in more recent HgbA1c using our small sample size, we would like to explore whether these relationships are significant, using larger data sets.